2012
DOI: 10.26719/2012.18.4.358
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns and oral health in schoolchildren from Damascus, Syrian Arab Republic

Abstract: This study investigated the association between dietary patterns and oral health in primary-school children from Damascus. A total of 504 children aged 6-12 years were enrolled and food frequency questionnaires were distributed to their guardians to evaluate food consumption. Dental health was evaluated by gingival index and presence of untreated dental caries. Consumption of food groups was lower than recommended frequencies, whereas consumption of sugars was high. High sugar consumption (OR 5.26), low consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 22 publications
0
21
0
1
Order By: Relevance
“…The consumption level of sugar in the Catholic Middle Eastern Canadian community is also higher than the one reported for Lebanese living in Beirut (11?4 % of daily energy intake) (15) . Elsewhere, higher levels of sugar intake (.20 % of daily energy intake) were reported in rural Egypt, mostly due to the consumption of sweetened tea (38) , as well as in children of aged 6-12 years who consumed sugary baked goods in Syria (39) . In the traditional diets of the Middle East region sweetened tea was consumed daily and home-prepared pastries and desserts were prepared and consumed on festivities (12)(13)(14) .…”
Section: Discussionmentioning
confidence: 99%
“…The consumption level of sugar in the Catholic Middle Eastern Canadian community is also higher than the one reported for Lebanese living in Beirut (11?4 % of daily energy intake) (15) . Elsewhere, higher levels of sugar intake (.20 % of daily energy intake) were reported in rural Egypt, mostly due to the consumption of sweetened tea (38) , as well as in children of aged 6-12 years who consumed sugary baked goods in Syria (39) . In the traditional diets of the Middle East region sweetened tea was consumed daily and home-prepared pastries and desserts were prepared and consumed on festivities (12)(13)(14) .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have found significant associations between the frequency of consumption of snacks, of foods high in sugars and the number of eating occasions with caries risk [Chankanka et al, 2011; Jaghasi et al, 2012; Marshall et al, 2005]. Also, inositol intake was higher during the morning and just before bedtime, particularly among children with caries, but no significant differences were seen between groups.…”
Section: Discussionmentioning
confidence: 88%
“…The presence of calculus has also been associated with the development of gingival recessions (5). Other risk factors associated to gingivitis include bad oral hygiene (9), economic inequalities (10), and high sugar consumption (9).…”
Section: Introductionmentioning
confidence: 99%